CsNIP5;1 acts as a multifunctional regulator to confer water loss tolerance in citrus fruit. (March 2022) - Zhang, Mingfei; Zhu, Yanfei; Yang, Hongbin; Li, Xin; Xu, Rangwei; Zhu, Feng; Cheng, Yunjiang
Highlights: Transgenic Arabidopsis overexpressing CsNIP5;1 showed more tolerance to osmotic and water loss stress. Overexpression of CsNIP5;1 significantly enhanced resistance to water loss in citrus callus and citrus fruit. CsNIP5;1 may affect the carbohydrate metabolism and water movement to alleviate water loss. Both CsWRKY4 and CsWRKY28 co-regulate CsNIP5;1 in the peel of harvested citrus fruit. Abstract: Plant aquaporins facilitate the transport of water across the inner membranes and play an important role in the response to water loss stress. A citrus NOD26-like intrinsic protein, CsNIP5;1, has been investigated to participate in the regulation of water permeability. In the present study, the expression profile indicated that CsNIP5;1 showed high transcription abundance in conducting tissues. Function analysis revealed that CsNIP5;1 reduced water loss of Arabidopsis rosette leaf, as well as promoted the seed germination under hyperosmotic stress. Besides, overexpression of CsNIP5;1 contributed to the alleviation of water loss in citrus fruit and citrus callus during storage. Further metabolomic profiling and RNA-seq analysis of transgenic citrus callus revealed that CsNIP5;1 may modulate the water loss by inducing the accumulation of osmotic adjustment substances and repressing the expression of other AQPs . Moreover, CsWRKY4 and CsWRKY28 were found to directly bind to the promoter and acted as opposite regulators of CsNIP5;1 during the postharvest period. These findings provide new insights into the regulatory mechanism of aquaporins in response to the water loss stress of citrus fruit during postharvest storage.